Forest Supply Chain for Bioenergy: An Approach for Biomass Study in the Framework of a Circular Bioeconomy - Manrique, Silvina Magdalena (2023)
To ensure the long-term viability of a circular bioeconomy based on native forests, it is crucial to enhance our understanding and overcome existing disparities in knowledge and application throughout the entire value chain of forest products. The objective of this article is to contribute towards this goal and facilitate the proper management of forest biomass. Firstly, a methodology is proposed for the study of biomass throughout the native forest value chain, identifying the main steps, criteria, and variables to consider. This approach is evaluated through a case study in Argentina, where over 2370 tons of biomass are wasted annually. A series of strategies for analyzing the most suitable uses and applications for this biomass are examined. Finally, some key approaches for the promotion of a circular and sustainable forest bioeconomy are identified. While it is true that there is still a long way to go before small rural economies can make a more efficient and comprehensive use of their resources (potentially including small biorefineries) with appropriate cascade use schemes, moving towards biomass energy use constitutes a practical and concrete alternative today. This proposal provides tools for accelerating this necessary ecological and energy transition.